Investigation of Study Procedures to Estimate Sensitivity and Reliability of a Virtual Physical Assessment Developed for Workplace Concussions: Method-Comparison Feasibility Study - Keely Barnes; Heidi Sveistrup; Mark Bayley; Mary Egan; Martin Bilodeau; Michel Rathbone; Monica Taljaard; Motahareh Karimijashni; Shawn Marshall (JMIR Neurotechnology)
Abstract BackgroundRemote approaches to workplace concussion assessment have demonstrated value to end users. The feasibility of administering physical concussion assessment measures in a remote context has been minimally explored, and there is limited information on important psychometric properties of physical assessment measures used in remote contexts. ObjectiveThe objectives of this feasibility study were to determine recruitment capability for a future larger-scale study aimed at determining sensitivity and reliability of the remote assessment, time required to complete study assessments, and acceptability of remote assessment to people with brain injuries and clinicians; document preliminary results of the sensitivity of the remote assessment when compared to the in-person assessment; and estimate the preliminary interrater and intrarater reliability of the remote assessments to inform procedures of a future larger-scale study that is adequately powered to reliably estimate these parameters of interest. MethodsPeople living with acquired brain injury attended 2 assessments (1 in-person and 1 remote) in a randomized order. The measures administered in these assessments included the finger-to-nose test; balance testing; and the Vestibular/Ocular Motor Screening (VOMS) tool, including documentation of change in symptoms and distance for near point convergence, saccades, cervical spine range of motion, and evaluation of effort. Both assessments occurred at the Ottawa Hospital Rehabilitation Center. After the assessments, a clinician different from the person who completed the original assessments then viewed and documented findings independently on the recordings of the remote assessment. The same second clinician viewed the recording again approximately 1 month following the initial observation. ResultsThe rate of recruitment was 61% (20/33) of people approached, with a total of 20 patient-participants included in the feasibility study. A total of 3 clinicians participated as assessors. The length of time required to complete the in-person and remote assessment procedures averaged 9 and 13 minutes, respectively. The majority of clinicians and patient-participants agreed or strongly agreed that they were confident in the findings on both in-person and remote assessments. Feedback obtained revolved around technology (eg, screen size), lighting, and fatigue of participants in the second assessment. Preliminary estimates of sensitivity of the remote assessment ranged from poor (finger-to-nose testing: 0.0) to excellent (near point convergence: 1.0). Preliminary estimates of reliability of the remote assessment ranged from poor (balance testing, saccades, and range of motion: κ=0.38‐0.49) to excellent (VOMS change in symptoms: κ=1.0). ConclusionsThe results of this feasibility study indicate that our study procedures are feasible and acceptable to participants. Certain measures show promising psychometric properties (reliability and sensitivity); however, wide CIs due to the small sample size limit the ability to draw definitive conclusions. A planned follow-up study will expand on this work and include a sufficiently large sample to estimate these important properties with acceptable precision.